2012
DOI: 10.3747/pdi.2011.00032
|View full text |Cite
|
Sign up to set email alerts
|

Effluent Free Radicals Are Associated with Residual Renal Function and Predict Technique Failure in Peritoneal Dialysis Patients

Abstract: ♦ Objective: Residual renal function (RRF) is associated with low oxidative stress in peritoneal dialysis (PD). In the present study, we investigated the relationship between the impact of oxidative stress on RRF and patient outcomes during PD. ♦ Methods: Levels of free radicals (FRs) in effluent from the overnight dwell in 45 outpatients were determined by electron spin resonance spectrometry. The FR levels, clinical parameters, and the level of 8-hydroxy-2′-deoxyguanosine were evaluated at study start. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 34 publications
0
22
0
4
Order By: Relevance
“…The fractional excretion of this nucleotide is increased in CKD patients because of the adaptive suppression of tubular reabsorption capacity (31). Recent studies indicate that preservation of residual renal function (RRF) has a beneficial effect in reducing the oxidative and carbonyl stress in PD patients (32,33). Given that most of our PD patients had some RRF, but that the HD patients were essentially all functionally anuric, it is reasonable to assume that urinary excretion of 8-OHdG in the PD patients could have contributed to lower serum levels.…”
Section: Discussionmentioning
confidence: 99%
“…The fractional excretion of this nucleotide is increased in CKD patients because of the adaptive suppression of tubular reabsorption capacity (31). Recent studies indicate that preservation of residual renal function (RRF) has a beneficial effect in reducing the oxidative and carbonyl stress in PD patients (32,33). Given that most of our PD patients had some RRF, but that the HD patients were essentially all functionally anuric, it is reasonable to assume that urinary excretion of 8-OHdG in the PD patients could have contributed to lower serum levels.…”
Section: Discussionmentioning
confidence: 99%
“…The Spearman rank correlation was used to determine the correlations between two variables. A multiple logistic regression analysis was applied to test the independent links between the vascular function and potential functional correlates of the outcome variables [71], [72]. A multivariable logistic regression analysis was performed to determine the predictors of baPWV.…”
Section: Methodsmentioning
confidence: 99%
“…In the light of studies that reported that for every 1 ml/min increase in residual renal function (RRF) in a peritoneal dialysis (PD) cohort there was a 50% reduction in the risk of death 1 and that a 250-ml increase in daily urine output was associated with a 36% reduction in mortality (reanalysis of the CANUSA study 2 ), preservation of RRF has become one of the most important goals in the long-term management of the patients on PD. Loss of RRF has subsequently been shown to be associated with many complications of chronic uremia: protein-energy wasting, [3][4][5][6] hyperphosphatemia, 6,7 left ventricular hypertrophy, 3,6,8 arterial stiffness, 9 anemia, 3,5,6 inflammation, 8 a poorer quality of life, 10,11 technique failure, 12 and ultimately patient death. 1,6,13,14 One of the strengths of PD is that this modality is associated with greater preservation of RRF when compared with hemodialysis (HD).…”
mentioning
confidence: 99%